РАДИОЭКОЛОГИЧЕСКИЙ ОТКЛИК ЧЕРНОГО МОРЯ НА ЧЕРНОБЫЛЬСКУЮ ЯДЕРНУЮ АВАРИЮ В ОТНОШЕНИИ ДОЛГОЖИВУЩИХ РАДИОНУКЛИДОВ 90Sr И 137Cs - Егоров, В. Н.; Поликарпов, Г. Г.; Освас, И.; Стокозов, Н. А.; Гулин, С. Б.; Мирзоева, Н. Ю. (Marine Ecological Journal, 2023)
This work is dedicated to the investigation of 90Sr and 137Cs fluxes of discharges to the Black Sea after Chernobyl NPP accident, migration of the radionuclides in the water environment, accumulation by hydrobionts and the dose commitment assessment for marine organisms as well as the prediction of the 90Sr and 137Cs time-scales of contents decrease in the different components of the Black Sea ecosystem to the pre-Chernobyl NPP accident levels. It was obtained, that 137Cs discharge to the Black Sea will exceed 35 years and will be 1740 – 2440 TBq or 1.7–6.6% from practically full amount injected into to the environment from the Chernobyl NPP accident reactor. The prognosis 90Sr discharge to the Black Sea will exceed 70 years and will be 305 - 505 TBq for this period or 3.7 - 38.8 % from its quantity injected into the environment after the Chernobyl NPP accident. The 137Cs discharge via Bospho-rus from the Black Sea will exceed 30 years, 90Sr – about 50 years. The radioactive contamination of the Black Sea hydrobionts after the Chernobyl NPP accident was not exceed maximum permissible levels of concentrations, their total dose commitments were in the “Physiological masking zone”and “Radiation well-being zone” limits.